(untitled) (English Language and Literature (JELL), 2026)
This research aimed to analyze the types of humor the characters employ and the violation or flouting of the conversational maxims contained in the humorous utterances that found in the movie. The data were humorous utterance that uttered by the characters in the movie Beetlejuice 2. This study applied a descriptive qualitative method to collect and analyze the data. The amount totals of data are 60 humorous utterances. The analysis revealed that the characters employed all four types of humor types: 21 data of Aggressive humor, 17 data of Affiliative humor, 17 data of Self-enhancing humor, and 5 data of Self-defeating humor. On the other hand, 54 out of 60 humorous utterances were found to contain violations and flouting of conversational maxims. The researcher concludes that among the four humor types identified, aggressive humor emerges as the dominant type used by the characters. Moreover, humorous utterances in Beetlejuice 2 frequently involve violations and flouting of conversational maxims, which function as key strategies in generating humor.